Pengaruh Fasilitas Wisata Terhadap Keputusan Berkunjung Kembali dengan Kepuasan Sebagai Variabel Mediasi, di Taman Wisata Alam Mangrove Angke Kapuk, Jakarta - Chairunnissa, Nur; Nurbaeti, Nurbaeti; Wulan, Saptarining; Mariati, Sri; Muhardiansyah, Doni (Jurnal Ilmiah Pariwisata, 2025)
This study aims to analyze the influence of tourism facilities on the decision to revisit the Angke Kapuk Mangrove Nature Tourism Park, Jakarta, with visitor satisfaction as an intervening variable. The approach used is quantitative with path analysis techniques. The research sample consisted of 400 respondents selected using purposive sampling techniques. The results of the study indicate that tourism facilities have a significant effect on visitor satisfaction, but do not directly affect the decision to revisit. Visitor satisfaction is proven to have a significant effect on the decision to revisit. In addition, tourism facilities have a significant effect on the decision to revisit through visitor satisfaction. Based on the results of the study, it is recommended that the management of the Angke Kapuk Mangrove Nature Tourism Park improve the quality of existing facilities, such as cleanliness, comfort, and accessibility, to increase visitor satisfaction. In addition, managers can pay attention to the emotional and social experience factors of visitors. For the DKI Jakarta government, it is recommended to support the management of this ecotourism with policies that pay attention to environmental sustainability and better infrastructure development. Keywords: tourism facilities, satisfaction, decision to revisit